2020
DOI: 10.2152/jmi.67.328
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oral condition and risk factors for jaw osteonecrosis in patients with hip fractures

Abstract: Purpose : Antiresorptive agents, such as bisphosphonates, are useful for the prevention of the recurrence of hip fractures. However, their administration has a risk of antiresorptive agent-related osteonecrosis of the jaw (ARONJ), and risk factors include poor oral hygiene. It is difficult for an orthopedic surgeon to examine a patient's oral condition thoroughly. This study evaluated the relationship between risk factors for ARONJ and intraoral findings in hip fracture patients. Materials and Methods : We eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Vandone et al in 2012 observed that after establishing preventive oral care measures, a lower number of cases of ONJ were observed [ 18 ], and Krimmel et al observed that drugs were not the only cause, but oral and dental health were crucial elements in the onset of this pathology [ 19 , 20 ]. Dental evaluation is evidently essential to avoid MRONJ, especially because the drugs involved in this disease are often the first therapeutical option for metabolic and oncologic patients, mostly keeping in mind the moderate incidence of this side effect [ 21 ]. At the same time, a paper by Al Abdullateef et al suggested that careful information about this kind of complication should be given both to dentists and patients, to avoid or delay the onset of complications [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vandone et al in 2012 observed that after establishing preventive oral care measures, a lower number of cases of ONJ were observed [ 18 ], and Krimmel et al observed that drugs were not the only cause, but oral and dental health were crucial elements in the onset of this pathology [ 19 , 20 ]. Dental evaluation is evidently essential to avoid MRONJ, especially because the drugs involved in this disease are often the first therapeutical option for metabolic and oncologic patients, mostly keeping in mind the moderate incidence of this side effect [ 21 ]. At the same time, a paper by Al Abdullateef et al suggested that careful information about this kind of complication should be given both to dentists and patients, to avoid or delay the onset of complications [ 22 ].…”
Section: Introductionmentioning
confidence: 99%